The Relationship between Biochemical and Hemoglobin Results and Quality Index Scores of the Mediterranean Diet of Pregnant Women in the First and the Third Trimester - Bulunc, Nazife Hurer; Yildiz, Emine (Mattioli 1885, 2021)
Introduction: The mother's nutrition and lifestyle during gestation is very essential for her own health as well as the infant's health. The aim of nutrition during gestation is both to keep the balance of nutrient factor spares in her body through meeting the physiological needs and to provide the necessary energy and nutrient factors for the normal growth of the fetus. Aim: This study was conducted with the purpose of analyzing the relationship between the biochemical and hemoglobin results and the quality index scores of the Mediterranean Diet in pregnant in the first and third trimester as well as comparing the biochemical and hemoglobin results of pregnant in the first and third trimester. Method: Total 30 pregnant participated in the research who were among 20-35 ages and were followed in a private hospital in Nicosia in Turkish Republic of Northern Cyprus. The demographic characteristics, nutrition habits, behavioral changes for nutrients during gestation were questioned and the anthropometric measurements were done. Also, in the first interview and in the III. trimester pre-prandial blood samples were obtained from the pregnant and analyses were done in a medical laboratory in terms of biochemical (Urea, Alanine amino Tranferase (ALT), Aspartate Amino Transferase (AST), pre-prandial blood glucose (PBG), Thyroid Stimulating Hormone (TSH), Creatinine, Free T4, folic acid, vitamin D (vit.), B-12 vit.) and hemoglobin analyses were done. The Mediterranean nutrition habit was evaluated by the Mediterranean Diet Quality Index (MDQI). Results: When the Mediterranean Diet Quality Index scores of pregnant in I. and III. trimester are analyzed, the average of the Mediterranean Diet Quality Index of I. and III. trimester were found as x =7.5 +/- 1.88, x =8.73 +/- 2.08 respectively, and the minimum score was 3, whereas the maximum obtained score was 12. There has not been a statistically meaningful correlation between the biochemical and hemoglobin findings of the pregnant in the I. trimester and the MDQI scores (p>0.05), whereas there has been a positive way meaningful correlation between the MDQI scores, and the AST values measured in the III. trimester (p<0.05). Also, there has not been a statistically meaningful difference between the vitamin B-12, vitamin D, folic acid, free T4, TSH, PBG and urea measured in pregnant in the I. trimester and III. trimester (p>0.05). In addition; there has been statistically meaningful difference between the values of creatinine, hemoglobin, AST and ALT values measured in the I. trimester and III. trimester (p<0.05). Conclusion: In order to have healthy child birth and development, the mothers' awareness needs to be raised in terms of protecting their health and also eating balanced and sufficiently due to the increase of the need for more nutrients during the gestation period.
Keywords: gestation; diet; Mediterranean; biochemistry; hemoglobin